1987
DOI: 10.1099/00221287-133-4-967
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Intracellular Inclusions and Plasmids in Xenorhabdus spp.

Abstract: Entomopathogenic bacteria of the genus Xenorhabdus produce crystalline inclusion bodies during in vitro culture. When cultured in liquid media, inclusions were present in primary forms but not secondary forms of X. nematophilus. In contrast, both primary and secondary forms of X. luminescens produced inclusion bodies during liquid culture. Two morphologically distinct forms of inclusion bodies were found in X. nematophilus subsp. nematophilus strain All. They were proteinaceous, and one of the proteins (IP-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…1987; Couche et al, 1987;Gregson & McInerney, 1985; To confirm that ppGpp induction is an obligatory step Paul et al, 1981 ; Rhodes et al, in the inhibition of RNA synthesis by the indole 1983; Richardson et al, 1988;Schmidt et al, 1988) antibiotic, its effect on the isogenic stringent and relaxed contribute to the success of the symbiotic relationship pair of E. coli K12 strains, NF161 and NF162 rewithin the microenvironment of the insect host. Among spectively, was investigated.…”
Section: Inhibition Of the Synthesis Of R N A And Proteinmentioning
confidence: 99%
“…1987; Couche et al, 1987;Gregson & McInerney, 1985; To confirm that ppGpp induction is an obligatory step Paul et al, 1981 ; Rhodes et al, in the inhibition of RNA synthesis by the indole 1983; Richardson et al, 1988;Schmidt et al, 1988) antibiotic, its effect on the isogenic stringent and relaxed contribute to the success of the symbiotic relationship pair of E. coli K12 strains, NF161 and NF162 rewithin the microenvironment of the insect host. Among spectively, was investigated.…”
Section: Inhibition Of the Synthesis Of R N A And Proteinmentioning
confidence: 99%
“…is not understood. No difference in plasmid composition between the two forms has been found (7,17). The structure of the bioluminescence (lux) genes has been found to be the same in the primary and secondary forms of the bacteria (10,23).…”
mentioning
confidence: 99%
“…Boemare et al (7) suggested that Xenorhabdus inclusions may be similar to the protein crystals of B. thuringiensis as both organisms are associated with entomopathogenesis. However, we have been unable to demonstrate toxicity of intact or solubilized inclusions when administered to Heliothis punctigera or Lucilia cuprina by either feeding or injection (10). Furthermore, hemolytic activity such as that associated with the 28-kDa protein of the B. thuringiensis var.…”
Section: Discussionmentioning
confidence: 98%
“…A subsequent survey of 11 strains of X. nematophilus and 2 strains of Xenorhabdus luminescens showed that all isolates were capable of producing inclusions when grown on solid media. In liquid media, inclusion formation occurred only in primary-form X. nematophilus, in contrast to X. luminescens in which both primary and secondary forms produced inclusions (10). Intracellular inclusion bodies have also been described in several ultrastructural studies of Xenorhabdus spp.…”
mentioning
confidence: 84%
See 1 more Smart Citation